The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1989
DOI: 10.1002/pola.1989.080270218
|View full text |Cite
|
Sign up to set email alerts
|

Polyamides containing arylene sulfone ether linkages

Abstract: Polyamides containing arylene sulfone ether linkages were synthesized from 4,4′‐[sulfonylbis(p‐phenyleneoxy)] dibenzoyl chloride (SPCI), 3,3′‐[sulfonylbis(p‐phenyleneoxy)] dibenzoyl chloride (SMCl), and arylene sulfone ether diamines (SED), by solution and interfacial polymerization techniques. In solution polymerization, the effect of various acid acceptors such as propylene oxide (PO), lithium chloride (LiCl)/lithium hydroxide (LiOH), and triethylamine (TEA) on molecular weight of the polyamides was studied.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 11 publications
1
18
0
Order By: Relevance
“…One of the main strategies in this filed is incorporation of flexible or kinked linkages, such as arylene ether into the polymer backbone [14][15][16]. We have also investigated the preparation of new polyamides with flexible linkages through design of novel monomers [17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 98%
“…One of the main strategies in this filed is incorporation of flexible or kinked linkages, such as arylene ether into the polymer backbone [14][15][16]. We have also investigated the preparation of new polyamides with flexible linkages through design of novel monomers [17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 98%
“…[7][8][9][10] Furthermore, they can maintain excellent physical, mechanical, and electrical properties over a wide temperature range. [11][12][13][14] In recent years, there is much literature about polyamide or polyimide containing sulfone groups, [15][16][17][18][19][20][21][22][23] whereas the studies on the modification of PUU or PU with sulfone have been less reported. Filip blended poly (ether sulfone) with PU elastomers.…”
Section: Introductionmentioning
confidence: 99%
“…However, the copolymers with the incorporation of rigid linkages, e.g., PPTA, are often difficult to be dissolved in organic solvents [4][5] . To address this problem, aryl ether linkages could be introduced into the main chain of them [6][7] .…”
Section: Introductionmentioning
confidence: 99%